Nanoarchitectonics in fully printed perovskite solar cells with carbon-based electrodes. Issue 7 (27th January 2023) - Bogachuk, Dmitry; Girard, Jessica; Tilala, Siddharth; Martineau, David; Narbey, Stéphanie; Verma, Anand; Hinsch, Andreas; Kohlstädt, Markus; Wagner, Lukas
Abstract : In this work, we demonstrate a novel nanoarchitectonic approach to tailor perovskite crystal growth leading to the enhancement of the opto-electronic properties and power conversion efficiency of perovskite solar cells. Abstract : A sacrificial film of polystyrene nanoparticles was utilized to introduce nano-cavities into mesoporous metal oxide layers. This enabled the growth of larger perovskite crystals inside the oxide scaffold with significantly suppressed non-radiative recombination and improved device performance. This work exemplifies potential applications of such nanoarchitectonic approaches in perovskite opto-electronic devices.